Visual Studio 2008 all-in-one desk reference for dummies - Leinecker, Richard C. (Wiley, 2008)
Visual Studio 2008 is packed with features that help you create better software and do it with less repetition and drudgery. Visual Studio 2008 All-In-One Desk Reference For Dummies shows you how to make the most of this cool suite of tools! It's all here! This comprehensive, seven-books-in-one guide gets you up and running with Visual Studio 2008 in no time. You'll discover Microsoft's vision for Visual Studio, get familiar with the .Net environment and languages, and learn how to install, browse, and make connections with Visual Studio. Soon, you'll be building applications for Vista, Offic.